2018
DOI: 10.3928/01913913-20180327-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cycloplegia on Optical Biometry in Pediatric Eyes

Abstract: Biometry measurements have to be carefully interpreted in pediatric eyes where cycloplegia is an important part of the examination. [J Pediatr Ophthalmol Strabismus. 2018;55(4):260-265.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Also, cycloplegia using 2% homatropine drops have been shown to reduce axial length measurements significantly in children between 5 and 15 years of age. 29 Possibly the use of cycloplegic drops therefore underestimates the true axial length values. As several studies described using cycloplegia for measuring refractive state, and others did not describe whether they used these drops, we decided not to distinguish between using cycloplegia or not.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cycloplegia using 2% homatropine drops have been shown to reduce axial length measurements significantly in children between 5 and 15 years of age. 29 Possibly the use of cycloplegic drops therefore underestimates the true axial length values. As several studies described using cycloplegia for measuring refractive state, and others did not describe whether they used these drops, we decided not to distinguish between using cycloplegia or not.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined the effects of highconcentration of atropine (1%) and tropicamide on ocular biological parameters in children, and calculated the changes of parameters before and after cycloplegia (difference value: post-cycloplegia minus pre-cycloplegia, absolute value of difference: |post-cycloplegia minus pre-cycloplegia|). In previous studies, some scholars had con rmed that cycloplegia in children could lead to changes in AL, K, CCT and ACD, among which the most studies on ACD increased observably [7,11,[13][14][15][16][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The ciliary paralysis reagents we used are mainly atropine as long-acting and tropicamide as short-acting. However, previous studies have shown that cycloplegia has a certain impact on ocular biological parameters, especially in children, including refractive state [10][11][12][13], axial length (AL) [11,[13][14][15][16], corneal curvature, axial position of corneal astigmatism, central corneal thickness (CCT) [10,[15][16][17][18][19],…”
Section: Introductionmentioning
confidence: 99%
“…Raina UK et al used Lenstar LS900 to study the axial length of 56 normal children aged 5 to 15 years, and found that after 2% homatropine cycloplegia, the axial length of these children was signi cantly shortened compared with that before medication. 19 Unfortunately, the study did not focus on the refractive status of children. Tang XP et al 20 used optical coherence biometry to measure the eye axis of children aged 4 to 11 years, and found that the eye axis of the hyperopia group was signi cantly shortened after atropine cycloplegic treatment, while the myopia group did not change signi cantly, and similar research conclusions were also supported by Wang LH et al 21 If the above studies were conducted using different cycloplegic agents, Woodman EC et al used IOL Master to measure the effect of continuous 5D accommodation near work for 30 minutes on the axial length of adult myopes and emmetropes, and found that near accommodation could signi cantly increase their axial length.…”
Section: Pupil Diametermentioning
confidence: 99%